A Handout IPA Berbasis Problem (HIPAPe): Materi Bumi dan Tata Surya melalui Framework Design Thinking - Rahmawati, Rahmawati; Sriwulan, Wiwin; Samsudin, Achmad (Universitas Sarjanawiyata Tamansiswa, 2024)
This research is a problem-based science handout development research (HIPAPe) that aims to find out how to motivate students to conduct scientific discussions and start liking literacy activities. This research uses a design thinking approach through several stages, namely emphatize, define, ideate, and prototype. The research method uses Design and Development Research (DDR). This research will develop and validate products in the form of Problem-based Science handouts (HIPAPe). HIPAPe has been validated by five expert validators. Data analysis was carried out by finding the validity value of V'Aikens and CRT and finding the reliability value using the SPSS application. Based on the results of data analysis in the form of V'Aikens of 0.75, based on this HIPAPe can be said to be valid. In addition, the results of the CRT analysis amounted to 60.5, meaning that HIPAPe can be said to be valid but there are minor improvements to the suggestions of the five validators. Then the reliability level is strong (reliability value of 0.625). Based on this, HIPAPe has a moderate ICC (Intraclass Correlation Coefficient) value or moderate reliability and can be said to have moderate reliability.